Changes in Metabolites Present in Lung-Lining Fluid Following Exposure of Humans to Ozone. (19th February 2018) - Cheng, WanYun; Duncan, Kelly E; Ghio, Andrew J; Ward-Caviness, Cavin; Karoly, Edward D; Diaz-Sanchez, David; Conolly, Rory B; Devlin, Robert B
Abstract: Controlled human exposure to the oxidant air pollutant ozone causes decrements in lung function and increased inflammation as evidenced by neutrophil influx into the lung and increased levels of proinflammatory cytokines in the airways. Here we describe a targeted metabolomics evaluation of human bronchoalveolar lavage fluid (BALF) following controlled in vivo exposure to ozone to gain greater insight into its pulmonary effects. In a 2-arm cross-over study, each healthy adult human volunteer was randomly exposed to filtered air (FA) and to 0.3 ppm ozone for 2 h while undergoing intermittent exercise with a minimum of 4 weeks between exposures. Bronchoscopy was performed and BALF obtained at 1 ( n = 9) or 24 ( n = 23) h postexposure. Metabolites were detected using ultrahigh performance liquid chromatography-tandem mass spectroscopy. At 1-h postexposure, a total of 28 metabolites were differentially expressed (DE) ( p < .05) following ozone exposure compared with FA-exposure. These changes were associated with increased glycolysis and antioxidant responses, suggesting rapid increased energy utilization as part of the cellular response to oxidative stress. At 24-h postexposure, 41 metabolites were DE. Many of the changes were in amino acids and linked with enhanced proteolysis. Changes associated with increased lipid membrane turnover were also observed. These later-stage changes were consistent with ongoing repair of airway tissues. There were 1.37 times as many metabolites were differentially expressed at 24 h compared with 1-h postexposure. The changes at 1 h reflect responses to oxidative stress while the changes at 24 h indicate a broader set of responses consistent with tissue repair. These results illustrate the ability of metabolomic analysis to identify mechanistic features of ozone toxicity and aspects of the subsequent tissue response.